Apple Peel Supplemented Diet Reduces Parameters of Metabolic Syndrome and Atherogenic Progression in ApoE−/− Mice. (17th May 2015) - Gonzalez, Jaime; Donoso, Wendy; Sandoval, Nathalie; Reyes, María; Gonzalez, Priscila; Gajardo, Monica; Morales, Erik; Neira, Amalia; Razmilic, Iván; Yuri, José A.; Moore-Carrasco, Rodrigo
Abstract : Cardiovascular Diseases (CVD) represent about 30% of all causes of death worldwide. The development of CVD is related in many cases with the previous existence of metabolic syndrome (MS). It is known that apple consumption has a cardiovascular protecting effect, containing phenolic compounds with antioxidant effect, which are concentrated in the fruit peel. The objective of this study was to test the effect of apple peel consumption in a murine model of MS and apoE−/− mice. Apple supplemented diets reduced the biochemical parameters (glycaemia, total cholesterol, HDL-cholesterol, LDL-cholesterol, ureic nitrogen, triglycerides, insulin, and asymmetric dimethylarginine (ADMA)) of MS model in CF1 mice significantly. The model apoE−/− mouse was used to evaluate the capacity of the apple peel to revert the progression of the atherogenesis. FD with HAP reverts cholesterol significantly and slows down the progression of the plate diminishing the cholesterol accumulation area. With these results, it can be concluded that the consumption of apple peel reduces several MS parameters and the atherogenic progression in mice.